Tarcze podatkowe miarą efektywności zarządzania podatkami - Falencikowski, Tadeusz; Nogalski, Bogdan (Tax Shields as An Efficiency Measure of Taxes Management, 2005)
This article shows measures which can be used to appraise efficiency of tax manager activities. The enterprise achieves these tax shields throughout tax management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 103-109